Effects of carbohydrate supplements and water on physiological parameters during exercise in the heat and humidity - Singh, Rabindarjeet; Sirisinghe, Roland G; Mat, Ishak; Nor, Norazmi Mohd (1999)
The aim of this study was to determine the effects of serial ingestion of carbohydrate-electrolyte beverages and a flavored water placebo (P) on physiological function during cycling performance in the heat and high humidity. Ten subjects participated in the experiment.In exercise experiment the subjects rode at 66.7±1.7% of maximal oxygen consumption to exhaustion in a room maintained at 31 .1 ±0.1 and 91.2±0.9% relative humidity on three separate occasions. During the rest and exercise bout the subjects consumed 3 mi. kg body weight-1 of P,a 6% carbohydrate-electrolyte (MC) or 12% carbohydrate-electrolyte (HC) beverage every 20 minutes. Beverage were administered in double blind, counterbalanced order.In the exercise experiment the total time to exhaustion was significantly longer for HC (84.7±6.9 min: P<0.001) and MC (75.3±3.5 min; P<0.01) compared to P (66.2±2.2 min).Compared to P, ingestion of the carbohydrate-electrolyte beverages resulted in higher glucose and insulin concentrations throughout the exercise with no significant differences in RER values.Markers of physiologic function and sensory perception changed similarly throughout exercise; no differences were observed among subjects in response to beverage treatment for changes in oxygen uptake, rectal and skin temperatures, heart rate, sweat rate, in plasma concentrations of lactate, sodium, potassium, ammonia, growth hormone, cortisol, creatine kinase, or for indices of gastrointestinal distress, perceived thirst, and overall beverage acceptance. Rating of perceived exertion, free fatty acids and glycerol levels at exhaustion were significantly higher in p trial. Although there was no significant difference in plasma volumes, it however resulted in a smaller change in MC during exercise in the heat and high humidity. Compare to ingestion of a water placebo, consumption of beverage contain 6% (MC) and 12% (HC) carbohydrate-electrolyte resulted in similar physiologic and sensory response, whilst ingestion of 12% carbohydrate-electrolyte beverage resulted in a longer exercise time to exhaustion in the heat and high humidity.